The morphology of the Luciąża River valley floor in the vicinity of the Rozprza medieval ring-fort in light of geophysical survey - Kittel, Piotr; Sikora, Jerzy; Wroniecki, Piotr (Bulletin of Geography. Physical Geography Series, 2015)
Multidisciplinary research (including magnetic survey, earth resistance survey, geological mapping, detailed archaeological surface survey and geochemical prospection) was undertaken on an area of about 0.7–9.0 hectares (depending on the method) in the close surroundings of the medieval ring-fort relicts in central Poland. The geophysical studies of the vicinity of the Rozprza ring-fort were part of a multi-method complementary non-destructive archaeological survey. The ring-fort is situated in the Luciąża River (Vistula River basin) valley floor and the flood plain morphology is very important for the reconstruction of palaeoenvironmental conditions of settlement location. Results of aerial photographs and geophysical prospection allowed the discovery of traces of sub-fossil palaeomeanders of different sizes as well as relicts of archaeological features (system of ramparts and moats). It was possible due to the application of high resolution archaeo-geophysical surveys. Both natural structures and also anthropogenic features registered with geophysics have been verified by geological sounding. The surface geology structure of the close vicinity of the ring-fort has been recognised in detail and selected organic deposits of palaeochannel fills and overbank covers have been 14C dated. The Rozprza ring-fort was situated in a defensive location on the surface of a sandy terrace remnant in the central part of a (partly) swampy valley floor. The accumulation of recorded fills of palaeochannels and moats covers the whole Holocene, as documented by 14C data. It gives the possibility for future detailed palaeoenvironmental studies. The results of geophysical studies, due to their known precise location, allow the effective planning of further research activities, both archaeological and palaeoenvironmental